If $\displaystyle S_{n}=\frac{x}{x+1}+\frac{x^2}{(x+1)(x^2+1)}+\frac{x^{2^{2}}}{(x+1)(x^2+1)(x^{2^2}+1)}+...........+\frac{x^{2^{n}}}{(x+1)(x^2+1)...(x^{2^{n}}+1)}$

Then $\displaystyle \lim_{n\rightarrow \infty}S_{n} = \;,$ Where $x>1$

$\bf{My\; Try::}$ First we will calculate $\bf{r^{th}}$ term of the sequence.

So $$\displaystyle \bf{T_{r}} = \frac{x^{2^{r}}}{(x+1)(x^2+1)............(x^{2^{n}}+1)} = \frac{x^{2^{r}}(x-1)}{x^{2^{r+1}}-1}$$

So We get $$\displaystyle \bf{T_{r}} = \frac{x^{2^{r}}(x-1)}{(x^{2^r}-1)(x^{2^{r}}+1)}$$

Now I did not Understand How can I convert into Telescopic Sum.

Help me


  • 1
    $\begingroup$ This may be helpful: $\frac{1}{(x^{2r}-1)(x^{2r}+1)}=\frac{1}{2}\Big(\frac{1}{x^{2r}-1}-\frac{1}{x^{2r}+1}\Big)$. $\endgroup$
    – Albert
    Dec 21 '15 at 8:22
  • $\begingroup$ Very interestingly, $$\lim\limits_{n\to\infty}\,S_n=x$$ for $x\in\mathbb{C}$ such that $|x|<1$. The unit disc $\big\{z\in\mathbb{C}\,\big|\,|z|=1\big\}$ is the natural boundary, but the series still converges at $x=1$ (to $1$). $\endgroup$ Oct 10 '19 at 14:57

$$\begin{align} S_{\infty}&=\frac{x}{x+1}+\frac{x^2}{(x+1)(x^2+1)}+\frac{x^{2^{2}}}{(x+1)(x^2+1)(x^{2^2}+1)}+\ldots+\frac{x^{2^{n}}}{(x+1)(x^2+1)\cdots(x^{2^{n}}+1)}\\\ &=\frac{x+1-1}{x+1}+\frac{x^2+1-1}{(x+1)(x^2+1)}+\frac{x^{2^{2}}+1-1}{(x+1)(x^2+1)(x^{2^2}+1)}+\ldots+\frac{x^{2^{n}}+1-1}{(x+1)(x^2+1)\cdots}\\\ &=1-\frac{1}{x+1}+\frac{1}{x+1}-\frac{1}{(x+1)(x^2+1)}+\frac{1}{(x+1)(x^2+1)}-\frac{1}{(x+1)(x^2+1)(x^{2^2}+1)}+\ldots\\\ &=1 \end{align} $$

The last term becomes vanishingly small as we increase $n$, that's why we can ignore it and say that the limit of $S_n$ as $n\to\infty$ is unity.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.